Financial Leverage, Corporate Investment, and Stock Returns - Ozdagli, Ali K. (Review of Financial Studies, 2012)
This article rationalizes empirical patterns of market leverage, book leverage, book-to-market ratios, and stock returns across different book-to-market portfolios, using a model of firm financing and investment. The model analytically shows that tax deductibility of interest payments increases effective investment irreversibility and that investment irreversibility weakens the relation between book-to-market values and returns. This provides a clear and novel mechanism showing how financial leverage affects stock returns beyond the standard Modigliani-Miller paradigm. The article argues that market leverage, rather than operating leverage or investment irreversibility, explains a major portion of the value premium. Empirical evidence supports this argument. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.